LEADERSHIP ROLE IN DECISION MAKING AND TEAM BUILDING IN SCHOOL - Ahmad Thoyib Mas'udi; Hasan Baharun; Fathor Rozi; Muhammad Ali Fadar Baihaki (Managere: Indonesian Journal of Educational Management, 2021)
This paper describes the role of leadership in decision-making and team-building at SMP Nurul Jadid Paiton Probolinggo. It is a qualitative approach with a case study type used in this research, and the data is being collected through interviews, observation, and documentation. The data analysis method employed is data reduction, followed by the presentation of the data and conclusion. According to the findings of the study, the leader's role in making decisions at the institution is as an entrepreneur, as a deterrent to distractions, as a resource divider, as a negotiator. At the same time, the role of leadership in building teamwork is showing his side, building an atmosphere or climate of mutual trust, respecting the ideas proposed by subordinates, prioritizing the comfort of his subordinates, taking into account the job satisfaction factors of subordinates, acknowledging the status of members of the organization appropriately and professionally, trying to sticking to commitments, views that teamwork is the best effort.